LBA20Keynote-407 China Extension study: Pembrolizumab (pembro) plus chemotherapy in Chinese patients with metastatic squamous NSCLC. (24th November 2019) - Cheng, Y; Zhang, L; Hu, J; Wang, D; Hu, C; Zhou, J; Wu, L; Cao, L; Liu, J; Zhang, H; Sun, H; Wang, Z; et al.
Abstract: Background: The primary analysis of OS and PFS in the randomized KEYNOTE-407 study, at median follow-up of 7.8 months, showed that pembro + carboplatin and paclitaxel/nab-paclitaxel (chemo) significantly improved OS (HR, 0.64 [95% CI, 0.49–0.85]; P < 0.001) and PFS (HR, 0.56 [95% CI, 0.45–0.70]; P < 0.001) vs placebo + chemo in patients (pts) with previously untreated metastatic squamous NSCLC. We present results from a prespecified interim analysis of the KEYNOTE-407 China extension (NCT03875092) study to assess outcomes in pts enrolled from mainland China vs a global population. Methods: The global and China extension studies were designed similarly. Pts from mainland China were randomized 1:1 to 35 cycles of pembro or placebo + 4 cycles of carboplatin and paclitaxel. Randomization was stratified by PD-L1 TPS (≥1%/<1%). Pts in the placebo + chemo arm with confirmed PD who met eligibility criteria could cross over to pembro monotherapy. Responses were assessed by RECIST v1.1 per blinded independent central review. Primary endpoints were OS and PFS. No alpha was allocated to this analysis. Results: 125 pts from mainland China were randomized to pembro + chemo (n = 65) or placebo + chemo (n = 60). At data cutoff (May 9, 2019), median follow-up was 10.4 months (range, 0.6–22.6). 58% of pts in the control arm had crossed over on-study to pembro monotherapy. Pembro + chemo improved OS, PFS, ORR, and DOR vs placebo + chemo (Table). Grade 3 − 5 AEs occurred in 89% and 87% of pts in the pembro + chemo and placebo + chemo arms, respectively; immune-mediated AEs and infusion reactions (any grade) occurred in 29% and 10%. Conclusions: Pembro + chemo improved OS, PFS, and ORR vs placebo + chemo, with a manageable safety profile, in pts from mainland China. These data are consistent with findings from the global study and support use of pembro + carboplatin and paclitaxel as a new standard of care for previously untreated metastatic squamous NSCLC in China. Clinical trial identification: NCT02775435, NCT03875092. Editorial acknowledgement: Vidya Ramachandran, PhD, of C4 MedSolutions, LLC (Yardley, PA, USA), a CHC Group company, and funded by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Legal entity responsible for the study: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Funding: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: J. Ge: Full / Part-time employment: MSD China. H. Wang: Full / Part-time employment: MSD China. Y. Tian: Full / Part-time employment: MSD China. B. Piperdi: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. L. Paz-Ares: Officer / Board of Directors: Genómica; Honoraria (self), Research grant / Funding (institution), Honoraria to self/spouse for scientific advice or as a speaker: AstraZeneca; Honoraria (self), Research grant / Funding (institution), Honoraria to self/spouse for scientific advice or as a speaker: Pfizer; Honoraria (self), Research grant / Funding (institution), Honoraria to self/spouse for scientific advice or as a speaker: BMS; Honoraria (self), Research grant / Funding (institution), Honoraria to self/spouse for scientific advice or as a speaker: MSD; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Roche; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Lilly; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Boehringer Ingelheim; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Novartis; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Amgen; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Merck; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Sanofi; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: PharmaMar; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Servier; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Sysmex; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Incyte; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Ipsen; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Adcap; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Bayer; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Blueprint Medicines; Honoraria (self), Honoraria to self/spouse for scientific advice or as a speaker: Celgene.